A prospective cohort study of head circumference and its association with neurodevelopmental outcomes in infants and young children in rural Guatemala. (22nd December 2022) - Connery, Amy K.; Lamb, Molly M.; Colbert, Alison M.; Bauer, Desirée; Olson, Daniel; Paniagua-Avila, Alejandra; Calvimontes, Mirella; Bolaños, Guillermo Antonio; Sahly, Hana M. El; Muñoz, Flor M.; Asturias, Edwin J.
Abstract: Microcephaly, an anthropometric marker of reduced brain volume and predictor of developmental disability, is rare in high-income countries. Recent reports show the prevalence of microcephaly to be much higher in lower resource settings. We calculated the prevalence of microcephaly in infants and young children (n = 642; age range = 0.1–35.9 months), examined trends in occipitofrontal circumference (OFC) growth in the year after birth and evaluated the relationship between OFC and performance on the Mullen Scales of Early Learning (MSEL) in rural Guatemala. Multivariable regression analyses adjusted for age were performed: (1) a model comparing concurrent MSEL performance and OFC at all visits per child, (2) concurrent OFC and MSEL performance by age group, and (3) OFC at enrollment and MSEL at final visit by age group. Prevalence of microcephaly ranged from 10.1% to 25.0%. OFC z -score decreased for most infants throughout the first year after birth. A significant positive association between continuous OFC measurement and MSEL score suggested that children with smaller OFC may do worse on ND tests conducted both concurrently and ∼1 year later. Results were variable when analyzed by OFC cutoff scores and stratified by 6-month age groups. OFC should be considered for inclusion in developmental screening assessments at the individual and population level, especially when performance-based testing is not feasible.